Engineering hierarchical nanotrees with CuCo2O4 trunks and NiO branches for high-performance supercapacitors. Issue 12 (3rd March 2017) - Qiu, Kangwen; Lu, Min; Luo, Yongsong; Du, Xiwen
Abstract : Hierarchical CuCo2 O4 @NiO core–shell nanotree arrays on porous nickel foam substrates are synthesized via a simple hydrothermal approach and further investigated as electrode materials for supercapacitors. Abstract : Nanotrees consisting of CuCo2 O4 trunks and NiO branches were hydrothermally grown on 3D nickel foam, they were then assembled into a supercapacitor which exhibits excellent performance, e.g. high specific capacitances of 2219 and 1405 F g −1 at current densities of 1 and 20 A g −1, respectively, and a long-term capacity retention of ∼95.3% after 10 000 cycles at a high current density of 20 A g −1 . Such values are the highest among similar core/shell-structured metal oxide electrodes reported in the literature. Many factors are identified to be responsible for the observations: the highly conductive 3D Ni foam substrate that totally eliminates binders and conductive additives; highly crystalline CuCo2 O4 trunks are directly grown on the conductive current collector, allowing fast electron transport; and the mesoporous NiO branches with a huge surface area facilitate fast ion diffusion and intimate electrode/electrolyte contact. In addition, the trunks and branches have redox reactions with anions and cations, respectively, from the electrolyte, both reactions contribute much to electrochemical charge storage.